Factors Influencing Selection Types of Contraception in Women of Childbearing - annisa annisa; Murdiningsih Murdiningsih; Heni Sumastri (Poltekkes Kemenkes Palembang, 2021)
The number of couples of childbearing age in Indonesia is 36,993,725 (61.29%) of the total household heads. Nationally, there are 23,361,189 family planning participants (63.14%) of the number of couples of childbearing age in Indonesia. In South Sumatra, the use of Long-Term Contraceptive Methods (MKJP) including Intra Uterine Device (IUD), Female Operation Method (MOW), Male Operation Method (MOP), and implants is still at 15.76%, which means that it has not met the national target of 17.80%. The government makes policies and strategies for the Population Family Planning and Development Program. Family to increase the use of Long-Term Contraception Methods. However, the use of contraception in the working area of ​​the Sekip Health Center is still 21.33% compared to the use of non-MKJP contraception. Objective: To determine the factors that influence the selection of contraceptive types in women of childbearing age at Sekip Health Center Palembang City. Methods: This research is a quantitative research research with an kuantitatif deskriptif research method with a cross sectional study design. The sample size in this study was 37 respondents with simple random sampling technique